Agricultural 4.0: Its implementation toward future sustainability - Yahya, N. (Springer Verlag, 2018)
Agriculture 4.0 refers to systems that employ drones, robotics, Internet of Things (IoT), vertical farms, artificial intelligence (AI), and solar energy. Through the integration of digital technology into farming practices, companies are able to increase yields, reduce costs, experience less crop damage, and minimize water, fuel, and fertilizer usage. For the consumer, this equals cheaper and better quality food. However, there are some of the complex challenges the crop production industry, along with diminishing production profit margins for farmers. To grow the food and to provide the world needs, crop production systems need innovative solutions to produce more in an environmentally, economically, and socially viable way. So, while the conceptual framework, intentions, and the scope revolving around Agriculture 4.0 are thought provoking and exciting at the first instance, its successful implementation is the main challenge in many countries all over the world. Â© 2018, Springer Nature Singapore Pte Ltd.